WAYS OF IMPROOVING CAR SAFETY IN THE EU TROUGH REGULATION (Perner's Contacts, 2018)
Road safety in the EU has improved significantly over the past decades, thanksto effective action taken at EU and national level to address road user behaviour,vehicles and infrastructure. As a result the EU roads are the safest world-wide.This increased safety can, to a large extent, be attributed to legislative requirementson safety of vehicles that have been introduced to road safety. The EU has,in the past, introduced mandatory fitting of electronic stability control systemson all vehicles and advanced emergency braking systems and lane departurewarning systems on trucks and buses, which contribute to the reduction of fatalcasualties in traffic by an estimated 5,000 a year. The full potential of these andfurther active safety technologies can only become reality with large-scaledeployment in vehicles on EU roads. The aim of this paper providesa comprehensive overview and proposes a way forward as regards improved vehiclesafety for the benefit of all road users, that is to say, all citizens of the EuropeanUnion.
Keywords: Active Safety, Intelligent Transport Systems, Intelligent Vehicle, Intelligent Vehicle Safety Systems, Passive Safety, Present Vehicle Safety Regulation, Regulation, Vehicle Safety